Characterization of beta-lactamase producing Enterobacterales isolated from an urban community wastewater treatment plant in Iran - Kamal Hasani; Hadi Sadeghi; Mehdi Vosoughi; Mehran Sardari; Meysam Manouchehrifar; Mohsen Arzanlou (Iranian Journal of Microbiology, 2023)
Background and Objectives: he occurrence and characteristics of Extended Spectrum- and AmpC-β-lactamase producing Enterobacterales (ESBL-PE and AmpC-PE) in an urban wastewater treatment plant (WWTP) were investigated. Materials and Methods: A total of 30 wastewater samples were collected from all sections of WWTP. Enterobacterales were isolated and identified using standard microbiological tests. The antibiotic resistance profile was determined by the Kirby–Bauer disk diffusion method. Phenotypic screening for ESBL-PE and AmpC-PE isolates was performed by double-disk synergy and boronic acid disk potentiation tests, respectively. The isolates were examined for AmpC- and ESBL-encoding genes by PCR and sequencing methods. Results: Among 146 Enterobacterales isolates, 8.9% (n=13) [ESBL-only; 5.48% (n=8) and ESBL + AmpC; 3.42% (n=5)] were ESBL-producers and 15.75% (n=23) [AmpC-only; 12.33% (n=18) and ESBL + AmpC; 3.42% (n=5)] AmpC-producers. Hafnia spp. with 33.33% (n=1/3) and E. coli with 20.58% (n=7/34) [ESBL-only; 17.64% (n=6/34) and ESBL + AmpC; 2.94% (n=1/34)] were the most common ESBL-producing bacteria. Enterobacter spp. with 37.50% (n=6/16) of isolates were the most common AmpC-producing organisms. ESBL- and/or AmpC-producing isolates were identified in all parts of the WWTP including 80% (n=8/10) of samples taken from effluent. Among ESBL-producing isolates, blaCTX-M, blaTEM, and blaSHV ESBL-encoding genes were found in 61.5% (n=8), 15.3% (n=2), and 7.7% (n=1) of isolates, respectively. All CTX-M-type enzymes belonged to the CTX-M-1 group and CTX-M-15 subgroup. blaTEM and blaSHV type genes belonged to blaTEM-20 and blaHSV-12 subtypes, respectively. blaDHA with 73.9% (n=17/23), and blaCIT and blaFOX with 30.4% (n=7/23) each, were the most common AmpC-encoding genes among AmpC-producing isolates. Overall, 75% of ESBL-producing and 55.5% of AmpC-producing isolates exhibited multi-drug resistance phenotypes. The organisms were most resistant against ampicillin (82.2%) nalidixic acid (43.8%) and cephalexin (41.1%). Conclusion: ESBL- and AmpC-producing Enterobacterales spp. with diverse genetic resistance backgrounds in WWTP effluent poses a significant risk to public health.